Advocate Assistance for Witnesses and Suspects in Criminal Investigation: A Due Process Perspective - Jhon Sahap Edward Panggabean; Mompang Lycurgus Panggabean; Aartje Tehupeiory (Journal of Law and Social Politics, 2026)
Background: Examination practices in criminal investigations continue to raise human rights concerns, including intimidation, restricted access to legal counsel, and changes in witness status to suspect without adequate legal protection. Objective: This study analyzes the role of attorney assistance for witnesses and suspects during criminal investigations within the framework of due process principles and examines legal protection issues for witnesses who may potentially be designated as suspects. Methods: This normative legal research employs statutory, conceptual, and case-based approaches by analyzing the Criminal Procedure Code (Kitab Undang-Undang Hukum Acara Pidana [KUHAP]), the New Criminal Procedure Code (Kitab Undang-Undang Hukum Acara Pidana [New KUHAP]), Constitutional Court decisions, and due process principles. Results: The findings reveal that the New KUHAP strengthens the rights of witnesses and suspects to receive attorney assistance; however, several obstacles remain, including law enforcement officers’ repressive paradigms, witnesses’ limited awareness of their legal rights, and inadequate protection of the right against self-incrimination. Conclusion: Strengthening regulatory frameworks, transforming law enforcement paradigms, and optimizing the role of attorneys during criminal examinations are essential to realizing a fair and humane criminal justice system grounded in due process principles.